A Recent Survey of GHG Emissions Reporting and Assurance. Issue 2 (12th February 2022) - Ryan, Judy; Tiller, Demi
Abstract: This paper describes research undertaken to understand current market practice in relation to greenhouse gas (GHG) emission reporting in New Zealand. Our research sampled 237 large New Zealand entities. The results show that 31% of entities were doing some form of voluntary GHG emission reporting. Of the entities reporting GHG emissions, 73% were reporting some Scope 3 emissions. The majority (51%) do not appear to get assurance for their GHG emissions reports. This is a useful benchmark to assess the level and development of GHG emissions reporting in the future. It indicates the approach reporting entities should take if future regulations and standards follow the current market practice.